STRATEGI DAN DAMPAK KENAIKAN HARGA KEDELAI TERHADAP LABA USAHA PENGRAJIN TEMPE DI SUKOHARJO, JAWA TENGAH - Murwanti, Sri; Sholahuddin, Muhammad (Universitas Muhammadiyah Surakarta, 2014)
The price of soybean in Indonesiasome times have soared uncontrollable. The producer (especially micro enterprises) of tofu and tempe are no longerable to produce in that situation. Consequently the amount of tofu and tempe are rarely in the market, meanwhile they are one of the important needs of Indonesian people. In fact, the government adopted a policy of instant such as remove import duties on imported soybeans. The policy was not strategic and could be fatal, because the country would be flooded by soybean imports.While farmers were getting ready to go out of business. With quantitative and qualitative approaches, this paper analyzed regarding (1)to analyze the impact of increasing soybean price to operating income of tempe producers with operating income analysis (2)to analyze strategy of adjustments made by the producers of tempe to preserve their business with in depth interview. This analysis concluded that Operating income declined more than a half. That condition is very hard to continue their business. If the capital of producers of tempe was not enough strong, they would be going out of their business. In such difficult conditions, they did innotive strategy by reducing the size of tempe though at the same price..